Performance analysis of a microcontroller-based overvoltage and overcurrent protection system - Uddin, Mohammad Iftekher; Rashid, Muhammad Mahbubur; Salam, Syed Munimus (AlamBiblio Publishers, 2025)
A microcontroller-based over-voltage and over-current monitoring and protection system has been developed to enhance the safety and reliability of electrical systems by automatically disconnecting the circuit under fault conditions. The system integrates a PIC18F2550 microcontroller, relay switches, transistors, current transformers (CT), potential transformers (PT), and other discrete components, with a Windows-based graphical user interface (GUI) programmed in Visual Basic and USB communication for real-time monitoring and control. The microcontroller processes voltage and current signals from the CT and PT, compares them against predefined threshold values, and activates the relay driver through a transistor when an over-voltage or over-current condition is detected, disconnecting the circuit after a brief delay to prevent damage. Experimental results validate the system's effectiveness; for example, it successfully triggered protection at 4.7 A against a 4.5 A current threshold and at 214 V against a 210 V voltage threshold. Various test scenarios confirmed the system’s reliability in identifying and responding to fault conditions. Compared to recent research, the proposed design demonstrates improved performance in detection speed, operational accuracy, and system simplicity, offering a robust and cost-effective solution for modern electrical protection needs